Salivary Diagnostics in HIV Infection using Rapid Oral Fluid Detection Kit - Sabitha Gokulraj (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) are two words that conjure up an image of fear, social stigma, suffering and finally death. Laboratory diagnosis is the only method to determine HIV infection. The most commonly used specimen for detection of HIV is blood. Other fluids like plasma, serum, oral fluid and urine could also be used. Oral fluid has various advantages - it is a safe to collect, the procedure is noninvasive and painless, infectious virus in oral fluid is rare making oral fluid sample more readily disposable, adequate oral fluid sample can be collected. Oral fluid based rapid HIV testing can be used as an alternative to serum as the biological fluid can be analyzed for diagnostic purposes. Oraquick was one such diagnostic rapid detection kit for the diagnosis of HIV infection. A study was conducted at Vinayaka Mission’s Sankarachariyar dental college and thus it was understood that rapid oral fluid testing is feasible and can be used for surveillance as well as part of a diagnostic algorithm, within the limit applicable to standard tests used for antibody detection.